Preschool teachers as undercover agents within the figured world of public school. (June 2018) - Sisson, Jamie Huff
This article explores the lived and sometimes clandestine professional experiences of early childhood teachers who exist within contexts where dominant discourses of professional are competing with teacher's own understandings of their professional identities. Cultural models theory is used to shed light on the secrete and undercover work of public preschool teachers as they resist the prevailing managerial discourse and assert their understandings of their professional identities behind the closed doors of their classrooms.